A discrete macro-model using homogenization with strain-rate dependency for the out-of-plane study of masonry panels subjected to impact loading - Silva, Luís C. (2017)
In recent decades, a great deal of effort has been made to develop solutions to reduce destructive damage and casualties due to blast loads and impacts, also in light of a major protection of the built heritage against terrorist attacks. In the present study, a simple and reliable Homogenization approach coupled with a Rigid Body and Spring Model (HRBSM) accounting for high strain rate effects is utilized to analyse masonry panels subjected to impact load. The homogenization approach adopted relies into a coarse FE discretization where bricks are meshed with a few elastic constant stress triangular elements and joints are reduced to interfaces with elastic-plastic softening behaviour including friction, a tension cut-off and a cap in compression. Strain rate effects are accounted for assuming the most meaningful mechanical properties in the unit cell variable through the so-called Dynamic Increase Factors (DIFs), with values from literature data. The HRBS model, which has been implemented at structural level in the commercial code ABAQUS resorts on a discretization into rigid quadrilateral elements with homogenized bending/torque non-linear springs on adjoining edges. The model is tested on a masonry parapet subjected to a standardized impact. A number of previous results obtained by literature models are available for comparison, as well as experimental data. Satisfactory agreement is found between the present results and existing literature in the field, both experimental and numerical.